Graphene oxide‐SiO2 hybrid nanostructure as coating material for capillary electrochromatography. Issue 10 (17th May 2016) - Qu, Qishu; Xuan, Han; Zhang, Kehua; Ding, Yi; Xu, Qin
Abstract : Graphene oxide (GO) has been considered as a promising stationary phase for chromatographic separation. However, the very strong adsorption of the analytes on the GO surface lead to the severe peak tailing, which in turn resulting in decreased separation performance. In this work, GO and silica nanoparticles hybrid nanostructures (GO/SiO2 NPs@column) were coated onto the capillary inner wall by passing the mixture of GO and silica sol through the capillary column. The successful of coating of GO/SiO2 NPs onto the capillary wall was confirmed by SEM and electroosmotic flow mobilities test. By partially covering the GO surface with silica nanoparticles, the peak tailing was decreased greatly while the unique high shape selectivity arises from the surface of remained GO was kept. Consequently, compared with the column modified with GO (GO@column), the column modified with GO and silica nanoparticles through layer‐by‐layer method (GO‐SiO2 NPs@column), or the column modified with silica nanoparticles (SiO2 NPs@column), GO/SiO2 NPs@column possessed highest resolutions. The GO/SiO2 NPs@column was applied to separate egg white and both acidic and basic proteins as well as three glycoisoforms of ovalbumin were separated in a single run within 36 min. The intra‐day, inter‐day, and column‐to‐column reproducibilities were evaluated by calculating the RSDs of the retention of naphthalene and biphenyl in open‐tubular capillary electrochromatography. The RSD values were found to be less than 7.1%.